Alpha activity emitted from leaves and roots of beetroot plant planted in enhanced soil with fertilizers - Ahmed Amin, Sahar (International Journal of Physical Research, 2020)
This study is to assesses radioactive materials transported to the beetroot plants grow in different fertilized soil. Equivalent weights of fertilizers were added to the soil prior the plantation. The alpha track densities were estimated utilizing solid state nuclear track detector (SSNTDs), CR-39. The obtained results show that alpha track densities in Beetroot plants in the lower and upper sides of plant leaves were varied from 67.62 Tr.cm−2 to 101.83 Tr.cm−2 and from 45.35 Tr.cm−2 to 94.67 Tr.cm−2 with mean values of 89.96 Tr.cm−2 and 68.48 Tr.cm−2, respectively. Alpha track densities were also measured in the samples of the enhanced plantation soil with fertilizers and in the whole parts of the Beetroot plant which were planted in these soils. These values were compared with alpha track densities obtained from fertilizer samples in the previous studies. The lower face of leaves gives higher α-particles activity than that obtained from the upper face. As well as, the alpha activity from the plants planted in soils enhanced with phosphate compost was found greater as contrast with that planted in a soil enhanced with organic fertilizer. The utilization of organic fertilizer don't cause much risks like contrasted with phosphate fertilizers. Therefore, the alpha activity depends on the nature of fertilizers added to the soil.